1970
DOI: 10.1111/j.1348-0421.1970.tb00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Immunity and Interferon Production in Macrophages

Abstract: The effect of antiserum on the interferon (IF) production in macrophages by Newcastle disease virus (NDV) has been studied. Completely neutralized NDV lost its IF-inducing ability, but under-neutralized NDV revealed an enhanced IFinducing capability. This enhancement of IF production by unneutralized NDV was also observed in antiserum-treated cells. Enhancement phenomena appeared to be based on immunological specificity. Under-neutralized NDV was also adsorbed more rapidly and at a higher rate to normal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1973
1973
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Such enhanced interferon production by immune macrophages has been reported by Glasgow (10) and Yamada et al (18). However, Glasgow (10) and Azuma et al (3) reported that increased ability of macrophages to produce interferon is specific for the immunizing virus, which is contrary to the results presented here. aPeritoneal macrophages harvested 10 to 14 days after tumor induction by subcutaneous inoculation of fibroma virus.…”
Section: Resultscontrasting
confidence: 99%
“…Such enhanced interferon production by immune macrophages has been reported by Glasgow (10) and Yamada et al (18). However, Glasgow (10) and Azuma et al (3) reported that increased ability of macrophages to produce interferon is specific for the immunizing virus, which is contrary to the results presented here. aPeritoneal macrophages harvested 10 to 14 days after tumor induction by subcutaneous inoculation of fibroma virus.…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, a four-fold increase of relevant interferon titers should be considered significant in this virus-cell system. However, the relationship between cytophilic antibody and neutralizing antibody is to date not known, whereas in the previous report [AzuM~ et al (2)] immunological specificity of antibody action in enhancement of interferon produetion was determined. Recently, Um~ (16) and HHAMAOKA and KITAGAWA (8) showed that macrophages interacted firmly with antigen eomplexing with antibody which was prepared by immunization of animals without Freund's complete ~djuvant and which was 19S and 7S y-globulin, and that the antibody did not operate as cytophilic antibody in the interaction of antigen-antibody complexes with macrophages.…”
Section: Discussionmentioning
confidence: 94%
“…AZUMA et al (2) demonstrated that under-neutralized NDV adsorbed on normal macrophages at a 50 % higher rate than did untreated NDV. By this under-neutralized NDV, a four-fold enhancement of interferon production, resulting from an increased multiplicity of virus, was observed (Table 1 and 4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation